The ties that bribe: corruption's embeddedness in Chicago organized crime - Joseph, Jared (Criminology, 2021)
The crime of corruption ranges from politicians involved in high-profile scandals to low-level bureaucrats granting contracts and police officers demanding bribes. Corruption occurs when state actors criminally leverage their positions of power for financial gain. Our study examines how corruption varies by political power position and within criminal contexts by measuring the embeddedness of corruption within Chicago historical organized crime. We analyze Chicago's organized crime network before and during Prohibition (1900–1919 and 1920–1933) to compare differences across embedded network positions between political, law enforcement, and nonstate actors. Our findings show that more police were in organized crime than politicians before Prohibition, but the small group of politicians had higher embeddedness in organized crime. During Prohibition, when organized crime grew and centralized, law enforcement decreased in proportion and became less embedded in organized crime. Politicians, however, maintained their proportion and high level of embeddedness. We argue that everyday corruption is more frequent but less embedded when criminal contexts are moderately profitable. As criminal contexts increase in profitability, however, corruption moves up the political ladder to include fewer people who are more highly embedded. This work has theoretical implications for the symbiotic relationship between corruption and criminal organizations.